Side‐sensitive modified group runs charts with and without measurement errors for monitoring the coefficient of variation. (19th September 2020) - Saha, Sajal; Khoo, Michael B. C.; Castagliola, Philippe; Haq, Abdul
Abstract: The coefficient of variation (CV) is used in process monitoring when the process mean and standard deviation are proportional to each other. In this work, a side‐sensitive modified group runs CV (SSMGR CV) chart is proposed for monitoring the process CV. The run length performance of the SSMGR CV chart is compared to those of the existing CV charts in terms of the average and standard deviation of the run length criteria. The SSMGR CV chart is found to outperform the existing CV charts. In addition, the run length performance of the SSMGR CV chart is also evaluated in the presence of measurement errors, as these errors are not only unavoidable in practice but they also affect the sensitivity of a control chart in detecting an out‐of‐control situation. The results obtained show that the accuracy and precision errors affect the performance of the SSMGR CV chart in detecting an out‐of‐control situation.